Board game design: an educational tool for understanding environmental issues. Issue 13 (2nd September 2021) - Parekh, Priyanka; Gee, Elisabeth; Tran, Kelly; Aguilera, Earl; Pérez Cortés, Luis E.; Kessner, Taylor; Siyahhan, Sinem
ABSTRACT: Framing, implementing, and engaging youth in authentic scientific inquiry are highly valued in science education; however, we have very limited knowledge of the nature and use of tools that accomplish these. Therefore, we proposed that board game design is a meaningful tool for engaging youth in understanding environmental issues. We reported findings from an educational board game design workshop based on real world issues for teens aged 13–17 years conducted at a large public library Makerspace. Using qualitative methods, we analysed the teens' process of making one such game, Pollutaplop, to understand its merits and argued that board game design nurtured the development of tools for inquiry. In response to the recent surge of interest in creating tools for learning about natural systems, we found that designing board games in authentic contexts engaged youth in building models as well as systems thinking. Intent gamers, including youth, might be well positioned to appreciate the complexities of both games and the contexts they are set in.